Diclofenac Sodium Solvent Extraction Based on Two‐Phase Flow Patterns. Issue 2 (27th November 2022) - Ansarimehr, Mahvash; Rahbar-Kelishami, Ahmad; Shayesteh, Hadi
Abstract: Diclofenac (DF) solvent extraction using tetra‐ n ‐butyl ammonium bromide (TBAB) in Y‐type microfluidic junctions with liquid‐liquid two‐phase flow patterns was investigated. The hydrodynamics of parallel, slug, and droplet flows were examined. The results indicated that the extraction efficiency decreased with increasing velocity. At Q O / Q A greater than 2.5, the flow pattern was converted from slug into droplet flow, and due to the enlargement of the specific surface area, the extraction efficiency increased. Slug flow provided an equilibrium extraction efficiency of 99.2 %. The overall volumetric mass transfer coefficient at different lengths and widths was evaluated. The best mass transfer performance occurred in microchannels with a length of 9 cm and a width of 400 µm. Abstract : Solvent extraction of diclofenac from aqueous solution using tetra‐ n ‐butyl ammonium bromide in Y‐type microfluidic junctions with liquid‐liquid two‐phase flow patterns was investigated. The hydrodynamics of parallel, slug, and droplet flows were examined. The effects of operating parameters and microchannel dimensions on mass transfer to achieve optimal conditions were also evaluated.